Simulation and analysis of flow in different geometrical arrays of a vascular graft (2010)
Blood flow dynamics has a fundamental role in the success of vascular grafts. In particular, shear stresses and secondary flows are involved in platelet activation and aggregation. In order to investigate these three dimensional flow characteristics, a program was developed and applied to the results of computational simulations. The program evaluates shear stress and residence time values to get a level of platelet activation. The used geometries are a simplification of real geometries obtained by injection-corrosion method and angiographic images. The partial results show that shear stresses reached abnormally high values in the anastomosis region, and presence of secondary flows in the post-anastomosis region.